The European Parliament heading towards icy Arctic waters – again - Raspotnik, Andreas; Stępień, Adam (Lapin yliopisto, Arktinen keskus, 2017)
The European Parliament’s new Arctic resolution on an integrated European Union policy for the Arctic was published on 16 March 2017. It is the EP’s fourth take on Arctic matters since its controversial position on Arctic governance back in 2008, and two follow-ups in 2011 and 2014. The document generally follows the lines drawn in previous EU Arctic policy statements: climate and environment, sustainability and regional development of the European Arctic.